Arousal and exposure duration affect forward step initiation - Bouman, Daniëlle; Stins, John F.; Beek, Peter J. (Frontiers in Psychology, 2015)
Emotion influences parameters of goal-directed whole-body movements in several ways. For instance, previous research has shown that approaching (moving toward) pleasant stimuli is easier compared to approaching unpleasant stimuli. However, some studies found that when emotional pictures are viewed for a longer time, approaching unpleasant stimuli may in fact be facilitated. The effect of viewing duration may modulate whole-body approach movement in previous research but this has not been investigated before. In the current study, participants initiated a step forward after viewing neutral, high-arousal pleasant and high-arousal unpleasant stimuli. The viewing duration of the stimuli was set to 7 different durations, varying from 100 to 4000ms. Valence and arousal scores were collected for all stimuli. The results indicate that both viewing duration and the arousal of the stimuli influence kinematic parameters in forward gait initiation. Specifically, longer viewing duration, compared to shorter viewing duration, (a) diminished the step length and peak velocity in both neutral and emotional stimuli, (b) increased reaction time in neutral stimuli and, (c) decreased reaction time in pleasant and unpleasant stimuli. Strikingly, no differences were found between high-arousal pleasant and high-arousal unpleasant stimuli. In other words, the valence of the stimuli did not influence kinematic parameters of forward step initiation. In contrast, the arousal level (neutral: low; pleasant and unpleasant: high) explained the variance found in the results. The kinematics of forward gait initiation seemed to be reflected in the subjective arousal scores, but not the valence scores. So it seems arousal affects forward gait initiation parameters more strongly than valence. In addition, longer viewing duration seemed to cause diminished alertness, affecting GI parameters. These results shed new light on the prevailing theoretical interpretations regarding approach motivation in the literature, which warrants further examination in future research.